Development of a butterfly check valve model under natural circulation conditions. (February 2015) - Rao, Yuxian; Yu, Lei; Fu, Shengwei; Zhang, Fan
Highlights: Bases on Lim's swing check valve model, a butterfly check valve model was developed. The method to quantify the friction torque T F in Li's model was corrected. The developed model was implemented into the RELAP5 code and verified. Abstract: A butterfly check valve is widely used to prevent a reverse flow in the pipe lines of a marine nuclear power plant. Under some conditions, the natural circulation conditions in particular, the fluid velocity through the butterfly check valve might become too low to hold the valve disk fully open, thereby the flow resistance of the butterfly check valve varies with the location of the valve disk and as a result the fluid flow is significantly affected by the dynamic motion of the valve disk. Simulation of a pipe line that includes some butterfly check valves, especially under natural circulation conditions, is thus complicated. This paper focuses on the development of a butterfly check valve model to enhance the capability of the thermal–hydraulic system code and the developed model is implemented into the RELAP5 code. Both steady-state calculations and transient calculations were carried out for the primary loop system of a marine nuclear power plant and the calculation results are compared with the experimental data for verification purpose. The simulation results show an agreement with the experimental data.